Extraction yield by hydrodistillation of Piper aduncum L. (matico) essential oil using a kinetic model - Fernández Rosillo, Frank (2024)
Essential oils are in demand in the food, pharmaceutical and cosmetic industries. The research aimed to estimate the extraction yield by hydrodistillation of Piper aduncum L. (matico) essential oil using a kinetic model. The methodology consisted of processing the plant material (harvesting, shade-drying and crushing matico leaves), extracting essential oil (hydrodistillation using two clevenger units under four scenarios) and modelling the kinetics of matico hydrodistillation extraction. The yield of matico essential oil in the four scenarios is in accordance with the mathematical model of sigmoidal kinetics. Therefore, the models determined provide a qualitative and approximate evolution of the behaviour of the extraction kinetics and the yield of matico essential oil.